Pengaruh Fitokimia Caffeine Terhadap Tekanan Darah : Literature Review - Afdilah, Irmawati Nur (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2025)
Caffeine is one of the most widely consumed stimulants worldwide, found in plants such as coffee, tea, and cocoa. This study aims to examine the effects of the phytochemical caffeine on blood pressure through a literature review. Caffeine consumption is known to influence the sympathetic nervous system and enhance alertness and cognitive performance. A literature review covering various studies from 2014 to 2024 reveals that caffeine has varying effects on blood pressure, depending on factors such as dosage, duration of consumption, and previous dietary habits concerning caffeine sources. The methodology used is a literature review, analyzing relevant journals and scientific articles to present data and draw conclusions regarding the relationship between caffeine consumption and blood pressure. The findings indicate that although caffeine can raise blood pressure in some individuals, this effect is not uniform and is influenced by various contextual factors. Therefore, caffeine consumption should be considered carefully, especially for individuals at risk of hypertension.